2016
DOI: 10.3892/etm.2016.3534
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic pre-administration reduces mortality in a mouse model of cecal ligation and puncture-induced sepsis

Abstract: Abstract. A number of clinical trials have demonstrated that the use of probiotics has the potential to prevent nosocomial infections. However, the mechanism underlying probiotic-induced anti-infection and sepsis remains to be investigated. In the present study, 200 µl/day of Lactobacillus rhamnosus GG (LGG) or normal saline (control) was orally administrated to 4-week-old C57BL6 mice 4 weeks prior to cecal ligation and puncture (CLP). A number of mice were sacrificed 24 h after CLP, and the remaining mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…A previous study demonstrated that septic mice pretreated with LGG had a markedly improved 7 day survival rate compared with the CLP+saline mice (P=0.029). Five sham mice survived (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that septic mice pretreated with LGG had a markedly improved 7 day survival rate compared with the CLP+saline mice (P=0.029). Five sham mice survived (10).…”
Section: Resultsmentioning
confidence: 99%
“…However, application of probiotics on sepsis has been limited due to the theoretical risk of aggravating bacteremia in patients with critical illnesses, although few data exist that support this concern (9). A previous study from our group has previously reported that prophylactic administration of a special probiotic bacterial species in a septic mouse model effectively reduced mortality (10). However, the underlying mechanisms by which probiotics alleviated the severity of sepsis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of probiotic bacteria contributes to intestinal function by maintaining paracellular permeability, enhancing the physical mucous layer, stimulating the immune system, and modulating resident microbiota composition and activity (Boirivant and Strober, 2007). Recently, Chen et al (2016) have reported that probiotic pre-administration could significantly reduce the mortality rate in a mouse model of CLP-induced sepsis. However, the underlying mechanisms of probiotics in regulating sepsis-induced gastrointestinal injury have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Early PMN recruitment to resolve the initial infection ( 155 , 156 ) and early administration of antibiotics ( 157 ) are both associated with increased survival rate. Also, pre-administration of probiotics ( 158 ) and mesenchymal stem cell transfusion ( 159 ) have both shown efficacy in reducing sepsis mortality in mice by suppressing infection and inflammation. Sepsis often results in acute respiratory distress syndrome (ARDS), with excessive PMN recruitment to the lung alveoli associated with increased mortality ( 160 ).…”
Section: Potential Therapeutic Pmn-specific Interventionsmentioning
confidence: 99%